Central Counterparties from the Islamic Finance Perspective - Karwowski, Jacek (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper focuses on central counterparties (CCPs) becoming the buyer to everyseller and the seller to every buyer and thereby ensuring the performance of opencontracts. The role of CCPs increased considerably after outbreak of the crisisin 2008.In 2012 BIS and IOSCO published the Principles for financial market (post-trade)infrastructures. The aim of the paper is to find out whether, and if yes – to whatextent, the mentioned principles have to be modified when applied to CCP servingIslamic financial institutions. It seems that all principles are appropriate forIslamic finance, however some of them should be modified in order to be Shariacompliant.Moreover, in some cases the modification might also be difficult dueto lack of standardized instruments.